Insight into Physicochemical, Rheological, and Antibacterial Properties of Chitosan Extracted from Antarctic krill: A Comparative Study - Yuan Yuan; Luzhu Chen; Wenzheng Shi; Zhihe Wang; Hongcai Zhang (Molecules, 2020)
In this work, physicochemical, rheological, and antibacterial properties of chitosan (CS) extracted from white shrimp (WS), giant river prawn (GP), and Antarctic krill (AK) were investigated. The results demonstrated that molecular weight (MW) of commercial chitosan (CCS), WSCS, GPCS, and AKCS were 1175.8, 2130.4, 1293.3, and 1109.3 kDa with the degree of deacetylation (DDA) of 73.5, 74.1, 82.1, and 75.9%, respectively. Fourier transform infrared (FT-IR), X-ray diffraction (XRD), differential scanning calorimetry (DSC), and scanning electron microscope (SEM) were employed to study the structural differences of CS. Moreover, storage modulus (G′) and loss modulus (G″) of AKCS were lower than that of WSCS and GPCS, respectively, but higher than that of CCS. Minimum inhibitory concentration (MIC) and minimum bacterial concentration (MBC) of CS against Escherichia coli and Staphylococcus aureus were investigated at concentration between 0.0125 and 1 mg/mL. These results highlighted that AKCS with low viscoelastic properties had a potential application in food and pharmaceutical application.